2014
DOI: 10.1177/2047487313518479
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Heart Age tool for improving modifiable cardiovascular risk factors in a Southern European population: a randomized trial

Abstract: Informing patients about their CVD risk expressed as the new Heart Age tool results in a reduction in their CVD risk higher than the one observed when the Framingham REGICOR risk score was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 21 publications
7
101
0
5
Order By: Relevance
“…For the four-level format variable (used in the main analysis), this was dummy coded (i.e., split into three dummy-coded variables). Lopez-Gonzalez et al, 2014). This research implies that the effective age format would be rated highest for understanding and behaviour change belief-not lowest, as we found.…”
Section: Studysupporting
confidence: 55%
See 2 more Smart Citations
“…For the four-level format variable (used in the main analysis), this was dummy coded (i.e., split into three dummy-coded variables). Lopez-Gonzalez et al, 2014). This research implies that the effective age format would be rated highest for understanding and behaviour change belief-not lowest, as we found.…”
Section: Studysupporting
confidence: 55%
“…There are, however, two forms of effective age: change (i.e., years older/younger) and personal age (i.e., your body as X years old). Those previous studies (e.g., heart age, Lopez-Gonzalez et al, 2014;lung age, Parkes et al, 2008), which have found a benefit to using effective age, have focussed on the personal age format (personalised heart or lung ages). Study 1, however, focussed on the "generic" change format, and its findings were opposite to those previous studies.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 New variants of the relative CVR are a) vascular age or risk age 9,83,84 , b) the age and gender total CVR percentile 83 and c) long-term (eg lifetime) risk approach 28 . There is no consensus about relative CVR thresholds of low, moderate, and high risk.…”
Section: Relative Total Cvrmentioning
confidence: 99%
“…In our study the data provided are considered to be altered when the heart age exceeds the chronological age by 1 year or more. This tool is very useful to motivate efforts to change unhealthy habits in the general population (13).…”
Section: Measurements and Calculationsmentioning
confidence: 99%